2011
DOI: 10.1016/j.pain.2010.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Attention to painful cutaneous laser stimuli evokes directed functional connectivity between activity recorded directly from human pain-related cortical structures

Abstract: Our previous studies show that attention to painful cutaneous laser stimuli is associated with functional connectivity between human primary somatosensory cortex (SI), parasylvian cortex (PS), and medial frontal cortex (MF), which may constitute a pain network. However, the direction of functional connections within this network is unknown. We now test the hypothesis that activity recorded from the SI has a driver role, and a causal influence, with respect to activity recorded from PS and MF during attention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
29
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 97 publications
(126 reference statements)
5
29
1
Order By: Relevance
“…Our prior studies of subdural recordings demonstrated the presence of critical sites that were associated with multiple significant ERC interactions in a laser attentiondistraction protocol (Liu et al 2011c). At critical sites, the numbers of ERC interactions during laser distraction and attention tasks were both larger than their median to a greater degree than expected at random.…”
Section: Erc Analysesmentioning
confidence: 86%
See 4 more Smart Citations
“…Our prior studies of subdural recordings demonstrated the presence of critical sites that were associated with multiple significant ERC interactions in a laser attentiondistraction protocol (Liu et al 2011c). At critical sites, the numbers of ERC interactions during laser distraction and attention tasks were both larger than their median to a greater degree than expected at random.…”
Section: Erc Analysesmentioning
confidence: 86%
“…In turn, the dDTF is a version of an earlier measure, the directed transfer function (DTF). The essential part of the ERC method is the statistical testing procedure that will reveal the significant changes in interchannel relationships after versus before the stimulus (i.e., event-related; Liu et al 2011c).…”
Section: Event-related Causalitymentioning
confidence: 99%
See 3 more Smart Citations